Cardiac troponin T concentrations above the 99th percentile value as measured by a new high-sensitivity assay predict long-term prognosis in patients with acute coronary syndromes undergoing routine early invasive strategy - Celik, Sultan; Giannitsis, Evangelos; Wollert, Kai Christoph; Schwöbel, Kerstin; Loßnitzer, Dirk; Hilbel, Thomas; Lehrke, Stephanie; Zdunek, Dietmar; Hess, A.; Januzzi, James L.; Katus, Hugo (Clinical research in cardiology, 2011)
A recently developed immunoassay for high-sensitivity measurement of cardiac troponin T (hsTnT) allows measurement at the 99th percentile for a normal population with an assay imprecision <10%. It is unclear whether such a low cutpoint (14 ng/L) is helpful for long-term risk stratification of patients with an acute coronary syndrome (ACS) undergoing routine early invasive strategy.
Gesehen am 28.06.2022